THE EFFECT OF MARKET VALUE ADDED AND ECONOMIC VALUE ADDED ON STOCK PRICES OF COMPANIES LISTED IN THE INDONESIAN SYARIAH STOCK INDEX (STUDY AT PT. TELKOM INDONESIA TBK 2012 – 2023) - Kifra Rizky Permana; Neneng Hartati (Lobi, 2025)
The capital market is very important in the Indonesian economy, especially as a source of long-term financing for companies. One of the instruments most sought after by investors is stocks, due to their high potential returns. It is suspected that Market Value Added (MVA) and Economic Value Added (EVA) have an influence on stock prices. In addition, previous studies have shown inconsistent results. This study aims to determine and analyze the partial effect of Market Value Added (MVA) on stock prices, the partial effect of Economic Value Added (EVA) on stock prices, and the simultaneous effect of MVA and EVA on the stock price of PT Telkom Indonesia Tbk during the period 2012–2023. The research method uses a descriptive quantitative approach, with data processed using SPSS for Windows Version 29. The results show that MVA has a partial significant effect on stock prices with a determination coefficient of 66%, while EVA does not have a partial significant effect with a determination coefficient of 12%. Simultaneously, MVA and EVA have a significant effect on stock prices with a combined determination coefficient of 66.8%, while the remaining 33.2% is influenced by other variables not examined in this study.